THE INFLUENCE OF COUNSELLING ON THE STUDENT KNOWLEDGE PRODI DIII LEVEL MIDWIFERY I IN THE Â EARLY DETECTION OF BREASTS CANCER THROUGH SADARI IN STIKES BINA SEHATPPNI MOJOKERTO - Puji Suryantini, Naning (JURNAL KEPERAWATAN BINA SEHAT, 2014)
ABSTRACTSADARI is effort or way of inspection of bosom which regularly and systematic conducted by itself woman representing shares not be locked out of by program of screening or detect early. Still many woman which do not know in doing SADARI. To increase the student’s knowledge was by giving health counselling. Target of this research is to know the influence of counselling on the student knowledge prodi DIII level Midwifery I in the early detection of breasts cancer through SADRI in STIKES BINA SEHAT PPNI Mojokerto year 2013 The kind of the pre-eksperimen ( design post-test pre-test group one). His population was all Student prodi DIII level Midwifery I with amount of sample 49 people. The Sampel election by using technique of proportional random sampling. Data collecting in this research propagate quesioner( pre-test) is later, then given by counselling is afterwards given by kuesioner again ( post-test). The analysis of the Data was carried out with editing, coding, and scoring. Result of the hypothetical test use the test wilcoxon. Result of the research showed that the student’s knowledge before counselling was 0% knowledgeable of goodness after was carried out by counselling increased to 19% and result of the willcoxon used softwere SPSS was obtained by by the vaive p= 0.000 α = 0.05 then Ho was refused that meant to have the influence of counselling on the student knowledge prodi DIII level Midwifery I in the early detection of breasts cancer through SADARI in STIKES BINA SEHAT PPNI Mojokerto. The increase to knowledge happened in joining counselling as well as the level of high education so as facilitated to accept information.Keyword :Counselling, knowledge, SADARI, student